2022
DOI: 10.3390/ijerph192013246
|View full text |Cite
|
Sign up to set email alerts
|

Between Policy and Risk Communication: Coverage of Air Pollution in Ghanaian Newspapers

Abstract: Mass media plays an increasingly persuasive role in orienting political decisions, shaping social agendas, influencing individuals’ actions, and interpreting scientific evidence for the public. With growing scientific understanding of the health, social and environmental consequences of air pollution, there is an urgent need to understand how media coverage frames these links, particularly in Low- and Middle-Income Countries. This paper examines how the Ghanaian print and electronic media houses are covering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…This mixed method study purposively identified three of the most vibrant digital news outlets in Ghana and did a content analysis of all GMO stories reported over three years from January 2021 to December 2023. We sourced data for this study from Ghanaweb.com, the most-read news website in Ghana; Myjoyonline.com, the second most-read news website in Ghana, and Graphic.com.gh, the digital platform of the most influential newspaper in Ghana, Daily Graphic 33–35 , 36 We used 8 keywords to search for all GMO-focused stories reported on these news websites over the period; GMO, GMOs, GM foods, GM Crops, Biotech crops, Biotechnology crops, Genetically modified crops, and Genetically Engineered Crops. We read through each of the articles and coded them manually, as was done by Lynas et al, 19 into one of 5 dominant issue categories; human health articles, food security articles, environment articles, sociocultural articles, and economics articles.…”
Section: Methodsmentioning
confidence: 99%
“…This mixed method study purposively identified three of the most vibrant digital news outlets in Ghana and did a content analysis of all GMO stories reported over three years from January 2021 to December 2023. We sourced data for this study from Ghanaweb.com, the most-read news website in Ghana; Myjoyonline.com, the second most-read news website in Ghana, and Graphic.com.gh, the digital platform of the most influential newspaper in Ghana, Daily Graphic 33–35 , 36 We used 8 keywords to search for all GMO-focused stories reported on these news websites over the period; GMO, GMOs, GM foods, GM Crops, Biotech crops, Biotechnology crops, Genetically modified crops, and Genetically Engineered Crops. We read through each of the articles and coded them manually, as was done by Lynas et al, 19 into one of 5 dominant issue categories; human health articles, food security articles, environment articles, sociocultural articles, and economics articles.…”
Section: Methodsmentioning
confidence: 99%
“…We argue that indirectly, over a longer period of time this may bring about changes in environmental policy as well. As previous studies suggest, the increased social and media attention to environmental issues may empower environmental activism, placing pressure on the government to respond to those salient environmental issues (Agyei-Mensah et al, 2022;Raja˜o & Jarke, 2018). In order to mitigate the political consequences of negative news and ensure better control over the situation, the government is likely to make policy responses.…”
Section: Theoretical Implicationsmentioning
confidence: 99%